Penerapan Problem Posing untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Muatan Pembelajaran Membaca Pemahaman - Lubis, Maulida Mandasari; Telaumbanua, Sadieli; Syahfitri, Dian (Universitas Nusantara PGRI Kediri, 2026)
This study is based on the fact that the development of 21st-century skills is very important, especially critical thinking skills, which until now are considered lacking in conventional learning methods. The purpose of this study is to determine how much influence the problem posing method has on students' ability to think critically during the reading comprehension learning process. This type of research is quantitative experiment. In grade XI of SMA Negeri 5 Tanjungbalai, students were divided into two groups. One group is the experimental class using the problem posing method, and the other is the control class using the conventional method. A test was used to assess critical thinking skills through reading comprehension. The results of the study illustrate that the problem posing technique improves students' ability to think critically with a mean of 88.77 compared to students using the conventional method with a mean of 82.17. According to the t-test, there is a significant difference (sig. (2-tailed) = 0.000 < 0.05), and the effect size produces a value of 1.14, which indicates that it is in the high category. These results indicate that problem posing is an effective technique for teaching students to think critically. This research shows that problem posing can be used as a learning method that encourages active student learning and improves critical and in-depth text comprehension.